Expression of Key Androgen-Activating Enzymes in Ovarian Steroid Cell Tumor, Not Otherwise Specified. (June 2020) - Valenzuela Scheker, Evana; Kathuria, Amita; Esnakula, Ashwini; Sasano, Hironobu; Yamazaki, Yuto; Tevosian, Sergei; Auchus, Richard J.; Ghayee, Hans K.; Dhir, Gauri
To characterize the expression of steroidogenic enzymes implicated in the development of ovarian steroid cell tumors, not otherwise specified (SCT-NOS). We present 4 ovarian SCT-NOS evaluated by immunohistochemical staining of steroidogenic enzymes as an approach to define this entity pathologically. All 4 ovarian SCT-NOS showed increased expression for cholesterol side-chain cleavage enzyme (CYP11A1), 17α-hydroxylase (CYP17A1), 17β-hydroxysteroid dehydrogenase 1 (HSD17B1), aldo-ketoreductase type 1 C3 (AKR1C3), 3β-hydroxysteroid dehydrogenase 2 (HSD3B2), 5α-reductase type 2 (SRD5A2), steroid sulfatase (SULT2A1), estrogen sulfotransferase (EST), and aromatase (CYP19A1). Expression was negative for 21-hydroxylase (CYP21A2) and 17β-hydroxysteroid dehydrogenase 2 (HSD17B2). 17β-hydroxysteroid dehydrogenase 3 (HSD17B3) and 5α-reductase type 1 (SRD5A1) showed variable expression. Our analysis reveals a novel finding of increased expression of AKR1C3, HSD17B1, SRD5A2, SULT2A1, and EST in ovarian SCT-NOS, which is clinically associated with androgen excess and virilization. Further studies are needed to validate these enzymes as new markers in the evaluation of hyperandrogenic ovarian conditions.